(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2024)
This research aims to describe the activities of Posyandu Kemuning which supports implementing the Early Childhood Development Program. The early childhood development program consists of health, nutrition and education services for early childhood in the community, especially for students at Hiama Kids Islamic School. This research uses a descriptive method with a qualitative research type. Data collection techniques were carried out through direct observation of Hiama Kids Islamic School Bogor students. Research data was collected through field notes, interviews with school principals, teachers, posyandu cadres, and parents, complete with data documentation and photos of activities. The results of the research show that the implementation of the program covering health, nutrition and education has not been carried out optimally because the posyandu activities are only carried out once a month.